Pengaruh Pengetahuan Produk Perbankan Syariah dan Motivasi Menghindari Riba Terhadap Keputusan Menjadi Nasabah Bri Syariah Cabang Jelutung Kota Jambi - Maulinda, Indah (Jurnal Ilmu Manajemen Terapan, 2023)
This study examines the influence of knowledge of Islamic banking products and motivation to avoid usury on the decision to become a customer of BRI Syariah, Jelutung Branch, Jambi City. This research is descriptive quantitative research with a survey method that was carried out at the BRI Syariah Jelutung Branch, Jambi City. The sampling technique uses the Slovin technique with a sample size of 100 customers. Hypothesis testing uses multiple regression analysis. This research resulted in three results, namely: (1) Product knowledge has a significant effect on the decision to become a customer at BRI Syariah Jelutung Branch, Jambi City. (2) Motivation to Avoid Riba has a significant effect on customer decisions at BRI Syariah Jelutung Branch, Jambi City. (3) Based on the results of simultaneous testing of product knowledge variables (X1) and motivation to avoid usury (X2) simultaneously have a significant effect on customer decisions (Y).